On the validity of Pelvicachromis sacrimontis Paulo, 1977 (Perciformes, Cichlidae), with designation of a neotype, and redescription of the species - Lamboj, Anton; Pichler, Christopher (Zootaxa, 2012)
Pelvicachromis sacrimontis Paulo, 1977 was originally described on the basis of an iconotype in an aquarium journal.Herein, the validity of the name as well as the species status is discussed, an updated diagnosis and description of thespecies is given, and a neotype and a series of paraneotypes is designated. The species differs from congeners in acombination of coloration features including a broad dark midlateral band, the absence of blue and reddish dots in the caudal fin of males, and the specific coloration of the dorsal fin in females.